Pengaruh model pembelajaran think talk write berbantuan google earth terhadap kemampuan menulis teks deskripsi peserta didik kelas iv sekolah dasar - Rahmah, Isna Nur Baeti; Yulisetiani, Septi (Universitas Sebelas Maret, 2025)
This research aims to determine the effect of using the Think Talk Write learning model assisted by Google Earth on the ability to write descriptive texts of fourth grade elementary school students. This research is motivated by the problems that occur in learning to write description texts in the form of difficulty determining and developing ideas, lack of writing practice, not writing the structure of the description text as a whole, not correctly writing punctuation, capital letters, standardized words, effective sentences, and word choice. Therefore, this research is important to use learning models and media that are interesting, interactive, and relevant to technological developments so that they can significantly optimize students' ability to write description texts. This research method is a quasi-experiment. The population of this study were all fourth grade students of elementary schools in Group II Banjarsari Sub-district, Surakarta City and selected using cluster random sampling. The data collection technique used a description text writing test. Test the validity of the research instrument with expert judgment, v-aiken, product moment, reliability rating results, and Cronbach Alpha. The research requirements test consisted of Kolmogorov-Smirnov normality test, Levene homogeneity test, and balance test. The results of independent sample t-test hypothesis testing showed a Sig. (2-tailed) 0.018 <0.05. The improvement in the ability to write description text by students has been able to describe objects concretely, write capital letters and punctuation correctly, use diction according to the topic, write effective and patterned sentences, write paragraphs that show the relationship between sentences, and the structure of description text is more complete than before. The implication of this research can be a consideration for teachers to use the same learning model in learning other materials in the future.